2009
DOI: 10.1097/qai.0b013e3181aac516
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Study of HIV-1 CRF01_AE Transmission in Hong Kong

Abstract: This is the first comprehensive molecular epidemiological study of HIV-1 CRF01_AE in Hong Kong. It revealed that MSM contact is becoming a major route of local CRF01_AE transmission in Hong Kong. Epidemiological linkage of CRF01_AE between Hong Kong and China observed in this study indicates the importance of regular molecular epidemiological surveillance for the HIV-1 epidemic in our region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…Infection with CRF01_AE as identified in this study has been confirmed through heterosexual transmission in China, and according to the recent reports MSM contact has become a major route of local CRF01_AE transmission in some cities of China and Singapore. [20][21][22] Our results suggest that MSM contact is becoming a major route of CRF01_AE transmission in China and that various forms of HIV transmission, including both homosexual and heterosexual behavior, likely exist among MSM of Liaoning province.…”
Section: Discussionmentioning
confidence: 94%
“…Infection with CRF01_AE as identified in this study has been confirmed through heterosexual transmission in China, and according to the recent reports MSM contact has become a major route of local CRF01_AE transmission in some cities of China and Singapore. [20][21][22] Our results suggest that MSM contact is becoming a major route of CRF01_AE transmission in China and that various forms of HIV transmission, including both homosexual and heterosexual behavior, likely exist among MSM of Liaoning province.…”
Section: Discussionmentioning
confidence: 94%
“…Prior HIV-1 molecular epidemiology studies performed in Asia were mainly focused on the transmission of locally predominant HIV-1 genotypes [7], [10], [13], [14]. There was limited number of studies which focused on new HIV-1 group M recombinant transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Through phylogenetic estimation, the divergence date of these strains in Hong Kong is around 1995–2001 [9], [10]. However, the prevalence of other new recombinant forms in Hong Kong remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, CRF01_AE, imported from surrounding countries and following drug trafficking routes, was detected in PWID in the provinces of Yunnan, Guangdong, and Guangxi in the mid-1990s (Beyrer et al, 2000; He et al, 2012; Yu et al, 1999). CRF01_AE strains, related to those circulating in Guangxi and other Chinese prefectures, have been identified in transmission clusters containing PWID in Hong Kong (Chen et al, 2009). Molecular analyses have showed that the CRF01_AE epidemics in China and Vietnam were monophyletic suggesting regional dispersal (Angelis et al, 2015).…”
Section: Molecular Epidemiology Of Hiv Among Pwid In Asiamentioning
confidence: 99%